Properties and Microstructures of Sn-Bi-X Lead-Free Solders - Fan Yang; Liang Zhang; Zhi-quan Liu; Su-juan Zhong; Jia Ma; Li Bao (Advances in Materials Science and Engineering)
The Sn-Bi base lead-free solders are proposed as one of the most popular alloys due to the low melting temperature (eutectic point: 139°C) and low cost. However, they are not widely used because of the lower wettability, fatigue resistance, and elongation compared to traditional Sn-Pb solders. So the alloying is considered as an effective way to improve the properties of Sn-Bi solders with the addition of elements (Al, Cu, Zn, Ga, Ag, In, Sb, and rare earth) and nanoparticles. In this paper, the development of Sn-Bi lead-free solders bearing elements and nanoparticles was reviewed. The variation of wettability, melting characteristic, electromigration, mechanical properties, microstructures, intermetallic compounds reaction, and creep behaviors was analyzed systematically, which can provide a reference for investigation of Sn-Bi base solders.